The analysis of the long-term outcomes of sorafenib therapy in routine practice in imatinib and sunitinib resistant gastrointestinal stromal tumors (GIST)* - Rutkowski, Piotr; Jagielska, Beata; Andrzejuk, Jolanta; Bylina, Elzbieta; Lugowska, Iwona; Switaj, Tomasz; Kosela-Paterczyk, Hanna; Kozak, Katarzyna; Falkowski, Slawomir; Klimczak, Anna (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study was to analyze the outcome of treatment and factors predicting results of sorafenib therapy in inoperable/metastatic CD117-positive GIST patients after failure on imatinib and sunitinib. Material and methods : We identified 60 consecutive patients (40 men, 20 women) with advanced inoperable/metastatic GIST after failure on at least imatinib and sunitinib treated in one sarcoma center with sorafenib at initial dose 2 × 400 mg daily in 2007–2015 (in 56 cases it was 3rd line therapy). Median follow-up time was 39 months. Results : One year progression-free survival (PFS; calculated from the date of the start of sorafenib to disease progression) rate was 23% and median PFS = 7.7 months. The median overall survival (OS) was 13.5 months calculated from sorafenib start (1-year OS rate = 57%) and 7 years from imatinib start. Three patients (5%) had objective partial responses to therapy, 31 patients (52%) had stabilization of disease > 4 months. Primary tumor mutational status was known in 43 cases (73%), but we have not identified the differences in PFS between tumors carrying different KIT/PDGFRA mutations. The most common adverse events were: diarrhoea, hand and foot syndrome, fatigue, loss of weight and skin reactions; grade 3–5 toxicity occurred in 35% of patients. 23 patients required sorafenib dose reductions due to AEs. Conclusions : We confirmed that many advanced GIST patients benefit from sorafenib therapy after imatinib/sunitinib failure with OS > 1 year.